2020
DOI: 10.1021/acsphotonics.0c00078
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Nanoparticles with Pure High-Order Multipole Scattering

Abstract: The ability to control scattering directionality of nanoparticles is in high demand for many nanophotonic applications. One of the challenges is to design nanoparticles producing pure highorder multipole scattering (e.g., octopole, hexadecapole), whose contribution is usually negligible compared to strong low-order multipole scattering (i.e., dipole or quadrupole). Here we present an intuitive way to design such nanoparticles by introducing a void inside them. We show that both shell and ring nanostructures al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 45 publications
(98 reference statements)
0
19
0
Order By: Relevance
“…[ 109,172,173 ] The initial experimental results suggest that, given a specific cavity‐to‐nanoantenna ratio, the gap structure may lead to an extremely enhanced local magnetic field in the center of the antenna. [ 174,175 ] However, the design of dielectric nanoparticles that produce high‐order multipole scattering (e.g., octopole, hexadecapole) but suppressed dipole modes remains a challenging task. Typically, the contribution of high‐order multipole modes to resonance in the visible region is negligible compared to intense low‐order modes (e.g., ED and MD modes).…”
Section: Manipulation Of the Scattering Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 109,172,173 ] The initial experimental results suggest that, given a specific cavity‐to‐nanoantenna ratio, the gap structure may lead to an extremely enhanced local magnetic field in the center of the antenna. [ 174,175 ] However, the design of dielectric nanoparticles that produce high‐order multipole scattering (e.g., octopole, hexadecapole) but suppressed dipole modes remains a challenging task. Typically, the contribution of high‐order multipole modes to resonance in the visible region is negligible compared to intense low‐order modes (e.g., ED and MD modes).…”
Section: Manipulation Of the Scattering Characteristicsmentioning
confidence: 99%
“…They showed that both ring and core–shell nanostructures supported almost pure high‐order multipole scattering. [ 175 ]…”
Section: Manipulation Of the Scattering Characteristicsmentioning
confidence: 99%
“…Namely, spheres with different sizes of the voids were used to show prevailing electric or magnetic octopoles scattering. It was also shown experimentally that disks allow the observation of electric octopole and magnetic hexadecapole scattering, depending on the inner diameter [6].…”
Section: Introductionmentioning
confidence: 96%
“…In what follows, we choose to analyse the emission properties of Si NPs, because of their high refractive index and low Ohmic losses, 26 the multitude of co-existing modes in the visible 27,28 -with the field largely confined inside the NP, thus calling for traversing electron beams-and the relatively large sizes required for the full glory of all Mie resonances to unveil itself; 29 the combination of these features can significantly pronounce the interference effects under study. The spectra of Mie-resonant NPs are characterised by multipoles of both electric and magnetic character, 30 Fano resonances, 31 anapoles, 32 and bound states in the continuum, 33 and have enabled functionalities as diverse as directional light scattering 34,35 and emission, 36 directional couplers, 37,38 and Huygens-based metasurfaces.…”
Section: Introductionmentioning
confidence: 99%